Analysis of current trends in the regional smart economy: challenges and prospects for Ukraine. - Verbivska, Liudmyla (Financial and Credit Activity Problems of Theory and Practice., 2022)
he formation of the economy based on knowledge-based innovative economy, new economy, at the present stage of social development is defining the international concept, according to which knowledge play a primary role, and their production is a source of economic growth and competitiveness. The economy is based on knowledge that provides a smart, sustainable and inclusive development. The purpose of the study. Showing that the implementation of the Strategy «Europe 2020», the main directions of the Fourth Industrial Revolution in the Ukraine will be able to provide smart, sustainable, inclusive development of the regions of Ukraine, will help to overcome the crisis and become a source for economic growth. Research methods. In the process of writing were used scientific methods, methods of analysis and synthesis, method of scientific abstraction. The results of the study. Macroeconomic instability has been transformed at the regional level, which led to the deepening of regions differentiation, particularly as it affected old industrial regions, including Donetsk and Luhansk. The crisis of public finances does not allow attracting of financial resources for economic development. As a result of hybrid war, the outflow of foreign investment amounted to 12.6 billion dollars USA. A significant part of the Donetsk and Luhansk regions is completely destroyed. Along with this, it’s perfect conditions in order to abandon the old and build new. There are all conditions to implement actively the European strategy «Europe 2020» and the main directions of the Fourth Industrial Revolution to a new stage of economic development, and ensure smart, sustainable and inclusive development of the regions of Ukraine. Conclusions and discussion position. The future of Ukraine and its regions depends on the activity of the Strategy «Europe 2020» and the main directions of the Fourth Industrial Revolution. In Ukraine, in the regions, the main emphasis is on export-oriented industries: coal, metallurgical, chemical, machine-building industry. Technically they are 3 and 4 technological structures, so they cannot become the breakthrough sectors of the Ukrainian economy, so the main emphasis should be on smart, sustainable and inclusive development.
Keywords: smart growth, sustainable development, inclusive growth, differentiation of regions, the Fourth Industrial Revolution